A Systematic Literature Review : Students’ Perception of Asynchronous and Synchronous in Learning - Ressy Novasyari; Melisa Novianty (Universitas Pahlawan Tuanku Tambusai, 2026)
The rapid development of digital technology has significantly transformed educational practices, particularly through the integration of synchronous and asynchronous learning modes.This article aims to conduct a systematic review of Students’ Perception of Asynchronous and Synchronous in Learning. The search strategy is based on the following keywords: